Improved Molecular Diagnosis of McCune–Albright Syndrome and Bone Fibrous Dysplasia by Digital PCR - Elli, Francesca Marta; de Sanctis, Luisa; Bergallo, Massimiliano; Maffini, Maria Antonia; Pirelli, Arianna; Galliano, Ilaria; Bordogna, Paolo; Arosio, Maura; Mantovani, Giovanna (Frontiers in Genetics, 2019)
McCune-Albright syndrome (MAS) is a rare congenital disorder characterized by the association of endocrine and nonendocrine anomalies due to somatic activating variants of GNAS. The mosaic state of variants makes the clinical presentation extremely heterogeneous depending on involved tissues. Biological samples bearing a low level of mosaicism frequently lead to false negative results with an underestimation of causative molecular alterations, and the analysis of biopsies is often needed to obtain a molecular diagnosis. To date, no reliable analytical method for the non-invasive testing of blood is available. This study was aimed at validating a novel and highly sensitive technique, the digital PCR (dPCR), to increase the detection rate of GNAS alterations in patients with a clinical suspicion of MAS and, in particular, in blood. We screened different tissues (blood, bone, cutis, ovary, and ovarian cyst) collected from 54 MAS patients by different technical approaches. Considering blood, Sanger was unable to detect mutations, the allele-specific PCR and the co-amplification at lower denaturation temperature had a 9.1% and 18.1% detection rate, respectively, while the dPCR reached a 37.8% detection rate. In conclusion, the dPCR resulted in a cost-effective, reliable and rapid method allowing the selective amplification of low-frequency variants, able to improve GNAS mutant alleles detection, especially in the blood.